More than 1,000 staff observe the spirit of independence - UMP, PNC
Close to 1,000 Universiti Malaysia Pahang (UMP) staff attended the launching of Merdeka Month Celebration and Fly the Jalur Gemilang campaign by Deputy Vice-Chancellor (Research & Innovation), Professor Dato’ Dr Rosli Mohd Yunus at Dewan Astaka, Gambang campus on August 16, 2011.